Health-related quality of life indicators among the adult population of Omsk Region: analysing the implementation of the DEMOGRAPHY national project - Yu. V. Menshchikova; E. A. Vilms; M. S. Turchaninova; E. V. Shcherba; A. V. Brusentsov (Фундаментальная и клиническая медицина)
Aim. To assess changes in health-related quality of life (HRQoL) parameters among the adult population of the Omsk region during the implementation of the Federal Project "Strengthening Public Health" as a part of the National Project "Demography." Materials and Methods. The study of HRQoL was conducted on representative quota samples, stratified by age, gender, and place of residence, in 2018 (n = 241) and similarly in 2023 (n = 506). The MOS SF-36 questionnaire was used to assess HRQoL, along with a number of visual analogue scale-based self-assessment questions concerning health. Results. HRQoL indicators showed higher values in 2023 across two scales reflecting both the physical component of health (BP – Bodily Pain, GH – General Health) and the psychological component (RE – Role Emotional Functioning, MH – Mental Health), as well as in the overall MCS scale, which characterizes the psychological health component. Among male respondents, higher values were recorded across all psychological component scales and in the two aforementioned physical health component scales. Among female respondents, improvements were observed in BP and the overall MCS scale. Self-assessed health, life satisfaction, and emotional well-being scores reported by respondents in 2023 were higher than in the previous assessment period. Conclusion. Positive changes in self-rated health assessment scales suggest a certain reassessment of health status by most of the population. Possible factors contributing to these changes include increased adaptive capacity, improved problem-solving skills, and measures implemented within the frameworks of the Demography and Healthcare National Projects.